Perancangan Geometri Ruas Jalan Gudang Cijambu STA 1+400 s/d STA 3+400 Menggunakan AutoCAD Civil 3D 2018 - Elkhasnet Elkhasnet; Nisa Fahira Sabillah (Institut Teknologi Nasional, Bandung, 2021)
ABSTRAKRuas jalan Gudang-Cijambu STA 1+400 s.d STA 3 + 400 di Sumedang, Jawa Barat berperan sebagai sektor penghubung distribusi hasil pertanian dari desa ke kota dan penunjang laju pertumbuhan ekonomi pedesaan. Dilakukan perancangan geometrik jalan baru menggunakan software AutoCAD Civil 3D yang mengacu pada AASHTO 2004 dan dibandingkan volume galian dan timbunan dengan perancangan konsultan. Hasil perancangan jalan baru secara manual dan menggunakan AutoCAD Civil 3D menghasilkan 9 lengkung horizontal sedangkan perancangan konsultan sebanyak 22 lengkung horizontal. Perancangan ulang menghasilkan panjang trase yang semula 2.000 m menjadi 1.747,41 m. Perancangan menggunakan data konsultan didapat selisih jumlah volume galian dan timbunan sebanyak 135.209,48 m³, ini lebih banyak dari perencanaan ulang dengan AutoCAD Civil 3D dimana selisih jumlah volume galian dan timbunan sebanyak 11.398,85 m³. Dengan AutoCAD, perancangan semakin mudah dan efisien dalam memilih trase.Kata Kunci: perancangan geometri jalan, trase, galian, timbunan ABSTRACTThe Gudang-Cijambu road section STA 1 + 400 s.d STA 3 + 400 in Sumedang, West Java acts as a connecting sector for the distribution of agricultural products from villages to cities and to support the rate of rural economic growth. In this study, a new geometric road design was carried out using AutoCAD Civil 3D software which refers to AASHTO 2004 and will compare the volume of excavation and fill with consultant design. The results of manual redesign and using AutoCAD Civil 3D resulted in 9 horizontal curves while consultant design was 22 horizontal curves. Changes in the number of bends and differences in PI coordinate points resulted in the length of the original line of 2,000 m to 1,747.41 m. Design using consultant data obtained a difference of 135,209.48 m³ of excavated and stockpile volume, more than the redesign with a difference of 11,398.85 m³ of excavated and stockpiled volume. With AutoCAD, design will be easier and more efficient to choose line.Keywords : geometric road design, line, excavated, stockpile